Borderlands Europe and the Mediterranean Middle East - Del Sarto, Raffaella A. (Oxford University Press, 2021)
The book proposes a profound rethink of the complex relationship between Europe-defined here as the European Union and its members-and the states of the Mediterranean Middle East and North Africa (MENA), Europe's 'southern neighbours'. These relations are examined through a borderlands prism that conceives of this interaction as one between an empire of sorts that seeks to export its order beyond the border, and the empire's southern borderlands. Focusing on trade relations on the one hand, and the cooperation on migration, borders, and security on the other, the book revisits the historical origins and modalities of Europe's selective rule transfer to MENA states, the interests underwriting these policies, and the complex dynamics marking the interaction between the two sides over a twenty-year period (1995-2015). It shows that within a system of structurally asymmetric economic relations from which Europe and MENA elites benefit the most, single MENA governments have been co-opted into the management of border and migration control where they act as Europe's gatekeepers. Combined with specific policy choices of MENA governments, Europe's selective expansion of its rules, practices, and disaggregated borders have contributed to rising socio-economic inequalities and the strengthening of authoritarian rule in the 'southern neighbourhood', with Europe tacitly tolerating serious violations of the rights of refugees and migrants at its fringes. Challenging the self-proclaimed benevolent nature of European policies and the notion of 'Fortress Europe' alike, the findings of this study contribute to broader debates on power, dependence, and interdependence in the discipline of international relations.